La conscience et l’autoconscience des futurs formateurs de FLE dans le développement de la compétence interculturelle - Dekhissi, Laurie; Lamprou, Effrosyni; Valetopoulos, Freiderikos (Glottodidactica, 2022)
In this paper, we analyse the degree of awareness and self-awareness of future teachers of French as a foreign language in teaching intercultural competence. To do so, we study extracts of students’ books created by the Master students themselves where the intercultural competence is developed. We realise that future Masters students are generally well aware of the need for intercultural mediation, however some of them focus on descriptive aspects of their culture rather than adopting a mediator posture, indeed they tend to describe and explain a cultural phenomenon rather than encouraging its interpretation and understanding.